THE CONDUCTOR - BETWEEN HEARING AND LISTENING - Aurel MURARU (Studia Universitatis Babeş-Bolyai. Musica, 2016)
The conducting activity operates with two specific types of auditory attention – on one hand, the attention designed to correct potential errors that may occur in the musical text, and, on the other hand, the auditory attention that is specific to the performing process, in itself. The present endeavour aims at emphasizing the characteristics of the conductor’s musical hearing, as well as its defining role in the art of conducting.